Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2015
DOI: 10.1097/bot.0000000000000354
|View full text |Cite
|
Sign up to set email alerts
|

Determining Stability in Posterior Wall Acetabular Fractures

Abstract: Diagnostic Level II. See Instructions for Authors for a complete description of levels of evidence.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
27
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(29 citation statements)
references
References 13 publications
0
27
0
1
Order By: Relevance
“…However, the image of the fractured acetabulum is sometimes covered by the femoral head, especially when the hip is dislocated. Using the software, the femoral head can be eliminated, and complete evaluation of the acetabular fracture pattern can be achieved [1517]. Posterior wall fragment size is one of the risk factors for the residual instability of hip joint after closed reduction [17].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the image of the fractured acetabulum is sometimes covered by the femoral head, especially when the hip is dislocated. Using the software, the femoral head can be eliminated, and complete evaluation of the acetabular fracture pattern can be achieved [1517]. Posterior wall fragment size is one of the risk factors for the residual instability of hip joint after closed reduction [17].…”
Section: Discussionmentioning
confidence: 99%
“…Using the software, the femoral head can be eliminated, and complete evaluation of the acetabular fracture pattern can be achieved [1517]. Posterior wall fragment size is one of the risk factors for the residual instability of hip joint after closed reduction [17]. However, there was no uniform method to calculate the percentage of posterior wall involvement.…”
Section: Discussionmentioning
confidence: 99%
“…These types of posterior wall fractures are all caused by the impact of the femoral head on the posterior wall of the acetabulum posteriorly 3 . Previous studies in the literature have adequately reported the treatment and prognosis of these types of posterior wall fractures, suggesting that anatomical reduction and internal fixation are key to achieving good outcomes, unless the hip remains stable 4,5 . However, in our clinical work, we found that both-column acetabular fractures are sometimes associated with posterior wall fractures (Fig.…”
Section: Introductionmentioning
confidence: 99%
“…The influence of acetabular version and impingement may be also closely involved in how challenging the determination of hip stability can be in patients with posterior wall acetabular fractures [9]. Acetabular retroversion and FAI may be related to the dislocation of unstable patterns with small fragments (wall sizes less than 20%) [10].…”
Section: Discussionmentioning
confidence: 99%